Proceedings of the IEEE 2002 International Interconnect Technology Conference (Cat. No.02EX519) (Proceedings of the IEEE 2002 International Interconnect Technology Conference : June 3-5, 2002, Hyatt Regency Hotel, Burlingame, CA, 2002)
The conference program begins with an address on the subject of Ambient Intelligence. This concept refers to the presence of a digital environment that is sensitive, adaptive and responsive to the presence of people. Subsequent presentation sessions address critical issues for ULSI circuits, low k dielectrics, advanced barrier materials and processes, interconnect system performance and reliability, copper/low k integration, and chemical mechanical planarization. Added features this year are new sessions on advanced packaging and optical interconnect that will introduce alternative solutions to the scaling problems facing conventional wiring technology.